A Graphene Surface Force Balance - Britton, Jude (Langmuir, 2014)
[Image: see text] We report a method for transferring graphene, grown by chemical vapor deposition, which produces ultraflat graphene surfaces (root-mean-square roughness of 0.19 nm) free from polymer residues over macroscopic areas (>1 cm(2)). The critical step in preparing such surfaces involves the use of an intermediate mica template, which itself is atomically smooth. We demonstrate the compatibility of these model surfaces with the surface force balance, opening up the possibility of measuring normal and lateral forces, including friction and adhesion, between two graphene sheets either in contact or across a liquid medium. The conductivity of the graphene surfaces allows forces to be measured while controlling the surface potential. This new apparatus, the graphene surface force balance, is expected to be of importance to the future understanding of graphene in applications from lubrication to electrochemical energy storage systems.